[BP.07.06] ACUTE ADMINISTRATION (SINGLE DOSE) OF BEETROOT JUICE ATTENUATES BLOOD PRESSURE DURING ISOMETRIC EXERCISE IN UNTREATED HYPERTENSIVE PATIENTS. (September 2017) - Triantafyllou, A.; Zafeiridis, A.; Papadopoulos, S.; Koletsos, N.; Gkaliagkousi, E.; Zafeiridis, A.; Grigoriadou, I.; Zamboulis, C.; Dipla, K.; Douma, S.
Abstract : Objective: Resistance (dynamic/isometric) exercise has been proposed for the management of blood pressure (BP) in hypertensive individuals, as an adjunct to aerobic exercise. Clinicians, however, are skeptical in prescribing resistance exercise to hypertensives as these patients may exhibit exaggerated BP responses during this mode of exercise. Dietary nitrate, in form of beetroot-juice (BRJ), has been shown to reduce BP during aerobic exercise in healthy and to induce BP and vascular benefits at rest in hypertensive individuals. However, the effects of BRJ-supplementation on the BP responses during exercise in hypertensives have not been investigated. This study examined whether a single BRJ-dose may reduce the BP response of hypertensives during exercise. Design and method: Thirteen, untreated, otherwise healthy, hypertensives (42.3 ± 12.3yrs.) participated in a double-blind, placebo-controlled trial. Each participant consumed, randomly, a nitrate-rich BR (8.1mmol NO3, BRJ) or a nitrate-depleted BR (Placebo) in two visits scheduled one week apart. Before and 2.5 hours after BRJ/placebo consumption, BP responses (Microlife), hemodynamic parameters (systemic vascular resistance and stroke indices) and arterial stiffness were assessed (Impedance Cardiography). Next, participants underwent an exercise protocol, consisting of a 3-min rest, a 3-min handgrip exercise (30% maximal voluntary contraction), and a 3-min recovery. Beat-by-beat BP were continuously assessed via photoplethysmography (Finapress). Results: At 2.5 hours post-juice consumption, resting BP (systolic/diastolic) was reduced compared with baseline in BRJ trial (p < 0.01), whereas, it was not significantly altered in placebo. No significant differences were observed in central hemodynamics and arterial stiffness between the pre- and post-juice consumption values in two trials. Prior to HG-exercise, during 3-min rest, there were no significant differences in BP between BRJ and Placebo. However, during HG-exercise, BP (mmHg) was significantly lower in BRJ vs. placebo (systolic BP: 173.3 ± 11.1 vs. 179.2 ± 13.9, p = 0.022; effect size d=0.47; diastolic BP: 100.7 ± 9.1 vs. 103.4 ± 5.2, p = 0.021; effect size d=0.38; mean BP: 129.9 ± 8.5 vs. 134.1 ± 6.0, p = 0.012; effect size d = 0.57). During the 3-min post HG-exercise, only the systolic BP was significantly lower in BRJ vs. Placebo (p = 0.054). Conclusions: A single-dose of BRJ consumption reduces BP during an isometric handgrip exercise protocol in newly diagnosed untreated hypertensive patients.